ANALISIS TINGKAT BEBAN KERJA MENTAL DAN KELELAHAN GURU DIMASA PANDEMI COVID-19 DENGAN METODE NASA-TLX DAN SOFI - ., Noverson; Nugroho, Adi (Universitas Muria Kudus, 2025)
The Coronavirus (Covid-19) pandemic has precipitated a paradigm shift in numerous facets of life, including educational institutions. In response to these challenges, governments have adopted online learning systems as a means to continue educational activities during periods of lockdown or social distancing. The implementation of online learning has been accompanied by a range of both advantages and disadvantages. As the rate of new infections began to decrease, the government permitted the resumption of in-person classes, albeit with a limited number of students. In response to this shift, Maitreyawira Junior High School Batam swiftly transitioned to a dual -shift learning model, effectively dividing students into two groups to ensure uninterrupted education. The objective of this study is to assess the mental load using the NASA-TLX (National Aeronautics and Space Administration Task Load Index) method and the level of fatigue using the SOFI (Swedish Occupational Fatigue Index) method. The objective of this study is to assess the mental load experienced by teachers during the period of remote learning due to the pandemic. The results of this study indicate that the level of mental load and mothers at Maitreyawira Junior High School Batam is in a very high category with a NASA-TLX score of 87.5 and the SOFI dimension of fatigue was moderate with score of 62,57.